Accountability, denial and the future-proofing of British torture. (1st May 2020) - Blakeley, Ruth; Raphael, Sam
Abstract: When powerful liberal democratic states are found to be complicit in extreme violations of human rights, how do they respond and why do they respond as they do? Drawing on the example of the United Kingdom's complicity in torture since 9/11, this article demonstrates how reluctant the UK has been to permit a full reckoning with its torturous past. We demonstrate that successive UK governments engaged in various forms of denial, obfuscation and attempts to obstruct investigation and avoid accountability. The net effect of their responses has been to deny the victims redress, through adequate judicial processes, and to deny the public adequate state accountability. These responses are not simply aimed at shielding from prosecution the perpetrators and those who have oversight of them, nor preventing political embarrassment. The various forms of denial and obstruction are also designed to ensure that collusion can continue uninterrupted. A core concern of intelligence officials and ministers has been to prevent any process that would lead to a comprehensive prohibition on involvement in operations where torture and cruel, inhuman and degrading treatment are a real possibility. The door remains wide open, and deliberately so, for British involvement in torture.